Acute generalized exanthematous pustulosis in a psoriasis vulgaris patient – diagnostic controversy - Wojas-Pelc, Anna; Dziunikowska, Anita (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Acute generalized exanthematous pustulosis (AGEP) is characterized by sudden onset of generalized pustular lesions on an erythematous-oedematous surface with accompanying general symptoms. In 90% of cases the disease has drug aetiology. The exact diagnosis may be difficult because of the clinical pattern resembling generalized pustular psoriasis. Objective. Presentation of diagnostic problems in a patient with common psoriasis and sudden appearance of generalized pustular eruption. Case report. We present a 52-year-old female patient with a positive history of psoriasis vulgaris, who was admitted to the hospital because of acute generalized pustular eruption probably caused by spironolactone and/or amlodipine. Skin symptoms were accompanied by general malaise, arthralgias and fever up to 38°C. Diagnosis of pustular psoriasis was established on the basis of morphology of skin lesions and positive psoriasis vulgaris history. Lack of improvement on acitretin therapy, appearance of new pustules with “iris-type” skin lesions, past history of macular drug eruption and scoring of patient’s symptoms at 7 points according to the diagnostic score of acute generalized exanthematous pustulosis established in 2001 by the EuroSCAR group resulted in change of the diagnosis to AGEP. Conclusion. Our case and the data from the literature clearly indicate that still there are no objective diagnostic criteria of acute generalized exanthematous pustulosis in patients with common psoriasis.